Effect of Occurrence of Lamin A/C (LMNA) Genetic Variants in a Cohort of 101 Consecutive Apparent “Lone AF” Patients: Results and Insights - Pessente, Gabrielle D'Arezzo; Sacilotto, Luciana; Calil, Zaine Oliveira; Olivetti, Natalia Quintella Sangiorgi; Wulkan, Fanny; Oliveira, Théo Gremen Mimary de; Pedrosa, Anísio Alexandre Andrade; Wu, Tan Chen; Hachul, Denise Tessariol; Scanavacca, Maurício Ibrahim; Krieger, José Eduardo; Darrieux, Francisco Carlos da Costa; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Mutations in the Lamin A/C(LMNA) gene are commonly associated with cardiac manifestations, such as dilated cardiomyopathy (DCM) and conduction system disease. However, the overall spectrum and penetrance of rare LMNA variants are unknown. The present study described the presence of LMNAvariants in patients with “lone atrial fibrillation (AF)” as their sole clinical presentation. Methods One-hundred and one consecutive patients with “lone AF” criteria were initially screened by genetic testing. Genetic variants were classified according to the American College of Genetic and Genomic criteria. All subjects were evaluated through clinical and familial history, ECG, 24-h Holter monitoring, echocardiogram, cardiac magnetic resonance, treatment response, and the present relatives of LMNA carriers. In addition, whole-exome data from 49,960 UK Biobank (UKB) participants were analyzed to describe the overall penetrance of rare LMNA missense and loss of function (LOF) variants. Results Three missense variants in LMNA were identified in probands with AF as their first and unique clinical manifestation. Other five first-degree relatives, after the screening, also presented LMNA gene variants. Among 49,960 analyzed UKB participants, 331 carried rare LMNA missense or LOF variant. Participants who carried a rare LMNA variant were significantly associated with higher odds of arrhythmic events and of an abnormal ECG in the per-protocol ECG exam (p = 0.03 and p = 0.05, respectively). Conclusion Although a rare occurrence, our findings emphasize the possibility of an initial presentation of apparently “lone AF” in LMNA gene variant carriers.